Web-Based Application Development for Applying Research or Internship Cover Letters at Kalbis Institute - Muhammad Hadits Alkhafidl; Yulia Ery Kurniawati (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This study aims to develop a web-based application for applying for research or internship cover letters at Kalbis Institute. The software development life cycle (SDLC) used the Rational Unified Process (RUP), and the software modelling used the Unified Modeling Language (UML). RUP has several phases. They are Business Modelling, Requirements, Analysis and Design, Implementation, Testing, and Deployment. The UML used a use case, activity, and class diagram. The application development used Visual Studio Code software with the PHP programming language. The results of this study are a web-based application for submitting research or internship cover letters for web admins and users. Web admin will be operated by academic operations while the users for students. All functional applications can run properly based on black box testing. The users, both academic operation administrators and students, agree that this application can help the administrators and students to process cover letters for research and internship at Kalbis Institute.